2013
DOI: 10.1186/1550-2783-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Cashew apple juice supplementation enhanced fat utilization during high-intensity exercise in trained and untrained men

Abstract: BackgroundExercise training is known to increase fat utilization during exercise. Diets containing antioxidants and branch chain amino acids (BCAAs) are also reported to have potential effects on fat utilization. Cashew apple juice (CAJ) comprises many nutritional components including vitamin C and BCAAs. This study aimed to investigate the effect of CAJ supplementation on substrate utilization during high-intensity exercise in trained and untrained subjects.MethodsTen trained and ten untrained men were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…Oxygen consumption and carbon dioxide production were measured throughout the test using a gas analysis system (AD instrument, ML206, Australia). The test was started with a 12 min 4-stage incremental test in which workload was increased every 3 min for 4 workloads [ 16 ]. The workload was determined from an estimate of the participants’ physical fitness status.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen consumption and carbon dioxide production were measured throughout the test using a gas analysis system (AD instrument, ML206, Australia). The test was started with a 12 min 4-stage incremental test in which workload was increased every 3 min for 4 workloads [ 16 ]. The workload was determined from an estimate of the participants’ physical fitness status.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it is possible that CAJ acts to attenuate the immunosuppressive effect following both overload training and a single bout of high-intensity exercise in sedentary individuals. Besides, CAJ supplementation was shown by our previous study to increase endurance and strength performance [6]. The improved performances may be due to the improved immune system, oxidative stress and stress hormone.…”
Section: Introductionmentioning
confidence: 96%
“…Cashew apple juice (CAJ), a product of cashew manufacturing, has been reported to improve immunological mechanisms by regulating balance between reactive oxygen species and antioxidant concentrations in mice [5]. Previous studies confirmed that four- and 12-week-consumption of CAJ elicited antioxidant effects in both untrained and trained subjects [6, 7]. That effect may have been due to its essential nutritional components, including vitamin C and anacardic acids, which have established antioxidant activity [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…After their first session of moderate-intensity exercise, individuals often experience muscle soreness because they do not have sufficient time to adapt to various factors such as increased mitochondrial activity leading to malondialdehyde (MDA) production from lipid peroxidation of the plasma membrane 3 , 4 ) . This phenomenon can cause muscle damage, leakage of creatine kinase (CK) 4 , 5 ) into the circulation, and inflammation 6 , 7 ) .…”
Section: Introductionmentioning
confidence: 99%